2022
DOI: 10.3389/fpls.2022.1057953
|View full text |Cite
|
Sign up to set email alerts
|

Frequent spontaneous structural rearrangements promote rapid genome diversification in a Brassica napus F1 generation

Abstract: In a cross between two homozygous Brassica napus plants of synthetic and natural origin, we demonstrate that novel structural genome variants from the synthetic parent cause immediate genome diversification among F1 offspring. Long read sequencing in twelve F1 sister plants revealed five large-scale structural rearrangements where both parents carried different homozygous alleles but the heterozygous F1 genomes were not identical heterozygotes as expected. Such spontaneous rearrangements were part of homoeolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…Phenotypic measurements recorded during the growing of the parents and the hybrid genotypes used in this study revealed that hybrids had a more robust plant architecture and higher dry seed weight than their parents (Table S24, Fig. 5 ), in concordance, with previous observations on this and other related hybrids (Hu et al 2021b ; Orantes-Bonilla et al 2022 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Phenotypic measurements recorded during the growing of the parents and the hybrid genotypes used in this study revealed that hybrids had a more robust plant architecture and higher dry seed weight than their parents (Table S24, Fig. 5 ), in concordance, with previous observations on this and other related hybrids (Hu et al 2021b ; Orantes-Bonilla et al 2022 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…The extent of these features in an allopolyploid model crop like B. napus also have potential implications in other polyploid crops where heterosis still remains to be exploited, such as wheat and potatoes (Steeg et al 2022 ). Patterns of expression and methylation dominance levels could also contribute a new level of understand regarding allele-specific gene expression (Fan et al 2020 ; Sands et al 2021 ), isoform expression (Vitting-Seerup and Sandelin 2019 ; Yao et al 2020 ; Golicz et al 2021 ), gene fusion and dosage (Mahmoud et al 2019 ; Serin Harmanci et al 2020 ; Bird et al 2021b ) as well as non-germline omics variations among F 1 plants and populations (Higgins et al 2018 ; Cortijo et al 2019 ; Orantes-Bonilla et al 2022 ; Quezada-Martinez et al 2022 ). Their role in heterotic gene expression patterns is ultimately also of interest for transcriptome-based genomic selection or hybrid performance prediction (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WGDs are among the most profound mutational changes observed in nature particularly because they result in global genomic redundancy, which has consequences that range from the gene to the population (Fox et al, 2020). At the gene level, genomic redundancy contributes to relaxation of selective constraints (Otto and Whitton, 2000; Douglas et al, 2015; Zhang et al, 2020; Conover and Wendel, 2022), transcriptional re-programming (Schnable et al, 2011; Combes et al, 2013; Yoo et al, 2013; Akama et al, 2014; Hu et al, 2016; Yang et al, 2016; Edger et al, 2017; RamĂ­rez-GonzĂĄlez et al, 2018; Oberprieler et al, 2019; Landis et al, 2020; Song et al, 2020), altered epigenetic regulation (Madlung et al, 2002; Salmon et al, 2005; Shcherban et al, 2008; Fulneček et al, 2009; Akagi et al, 2016; Chen et al, 2017; Song et al, 2017; Ding and Chen, 2018; Rao et al, 2023), transposable element expansion (Ågren et al, 2016; Baduel et al, 2019), altered rates of homologous, ectopic, and intergenomic recombination (Chalhoub et al, 2014; Guo et al, 2014; Jarvis et al, 2017; Chen et al, 2018; Bertioli et al, 2019; Mason and Wendel, 2020; Gonzalo et al, 2023), chromosomal structural changes (Chester et al, 2012; Edwards et al, 2017; Gordon et al, 2020; Cai et al, 2021; Orantes-Bonilla et al, 2022), among a host of other fundamental changes to genome biology (Otto, 2007; Leitch and Leitch, 2008; Doyle and Coate, 2019; Bomblies, 2020), all of which have the potential to directly impact organismal function and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies in resynthesized polyploids showed extensive genetic changes in a short period of time (Song et al 1995). Subsequent investigations showed major genome structural changes from the first meiosis after polyploid formation, primarily in the form of homoeologous exchanges which can result in partial or complete deletion and duplication of chromosomal segments (Sharpe et al 2005; Osborn et al 2003; Jenczewski et al 2003; Pires et al 2004; Gaeta et al 2007; Nicolas et al 2007; 2012; Szadowski et al 2010; Xiong et al 2011; Chalhoub et al 2014; He et al 2017; Rousseau-Geutin et al 2017; Samans et al 2017; Stein et al 2017; Hurgobin et al 2018; Lloyd et al 2018; Pele et al 2018; Mason and Wendel 2020; Bayer et al 2021; Chawla et al 2021; Ferreira de Carvalho et al 2021; Higgins et al 2021; Xiong et al 2021; Orantes-Bonilla et al 2022). These rearrangements continue to accumulate over time, generating genomic diversity in early polyploids (Gaeta and Pires 2010; Xiong et al 2011; Mason and Wendel, 2020; Bird et al 2021).…”
Section: Introductionmentioning
confidence: 99%